Exploring the teaching and learning of Apartheid as a controversial issue in Grade 11 History classrooms - Mazibuko, Londeka (University of the Free State, 2024)
Teaching about apartheid as one of the controversial topics in History classrooms in South Africa presents challenges, such as the inability of teachers to address every aspect of apartheid. Apartheid was a system of racial ideology that encouraged social and political segregation and discrimination, existing from 1948 to 1994 in South Africa. The study explored History teachers’ understanding of the term "controversial issues" in the context of History. Furthermore, the study examined the challenges experienced by History teachers when teaching about apartheid. In addition, this study explored the teaching strategies that teachers use to enhance the teaching of apartheid, which is a controversial issue. There is a notable gap in how experienced History teachers handle the teaching of apartheid history as a controversial issue and how this has impacted the historical understanding among learners. The study draws from caring pedagogy as a theoretical framework to explore how History teachers navigate the teaching and learning of apartheid as a controversial issue in Grade 11 History classrooms. This study used the interpretivism research paradigm and phenomenological research design. The qualitative study collected data in one of the rural towns of Bergville and Estcourt, located in the uThukela District in KwaZulu-Natal. In this study, I used semi-structured one-on-one interviews to collect data from five professional teachers who have at least five years of experience teaching History in Grade 11, alongside existing texts for History teaching in South Africa. The findings revealed that teachers understood controversial issues as topics that do not allow for a common understanding among people regarding a particular issue. Furthermore, the data suggested that teachers experience challenges such as learners' lack of interest in the importance of learning about apartheid and in acquiring historical skills. This study indicates the importance for teachers and pre-service teachers to develop effective strategies to promote learners’ interest in the subject and assist them in attaining historical skills.
Dissertation (M.Ed. (Subject Education in Social Sciences))--University of the Free State, 2024
Keywords: Apartheid; Controversial issues; Grade 11 History; Teaching and learning; Social sciences education; History teaching